Human Papillomavirus Vaccine Sources of Information and Adolescents' Knowledge and Perceptions - Brittany L. Rosen PhD, CHESⓇ; Marcia L. Shew MD; Gregory D. Zimet PhD; Lili Ding PhD; Tanya L. K. Mullins MD, MS; Jessica A. Kahn MD, MPH (SAGE Publishing, 2017)
Understanding where adolescents obtain information about human papillomavirus (HPV) vaccines may be helpful in designing public health interventions promoting HPV vaccination. This study assessed the following: (1) exposure to specific sources of information about HPV vaccines, (2) self-reported helpfulness of these sources of information, and (3) whether the specific source of information was associated with knowledge and perceptions about HPV vaccines among adolescent girls. There were 339 adolescent girls (mean age = 16.8 years) recruited into the study. Television advertisements, the Internet, doctors/nurses, and mothers were the most frequently reported sources of vaccine information; more than 90% of participants who received information from these sources reported they were helpful. Adolescents who received information about HPV vaccines from television advertisements, the Internet, clinicians, and mothers had higher knowledge about HPV vaccines and more positive perceptions. Assuring the accuracy of messages from these sources will be essential, given their importance in influencing adolescents' knowledge and perceptions about HPV vaccines.